HUMAN RIGHTS IN WORLD HISTORY - Stearns, Peter N. ([S.l.])
1 online resource
Keywords: This book takes a global historical perspective to trace the rise of human rights and their global impact from the 18th century to the present. This fully updated volume examines the complex relationships between Western concepts of human rights and developments in other world regions. After providing background on relevant premodern concepts and constraints, the book explores regional interactions with human rights, the disastrous impact of imperialism and racism, the recurrent expansion of the range of rights given to those including women and children, and indigenous rights from the 19th century to the present. Major revisions for the second edition include: a new chapter focusing on recent historical and interdisciplinary debates a separate chapter on developments between the world wars greater attention to causation and an expanded treatment of some regions, including Africa an analysis of the mix of setbacks and rights expansion during the past15 years, within the global framework. Human Rights in World History is essential reading for students, scholars, and researchers interested in modern history, human rights, and political science.